TAILORING EXTENSIVE READING PROGRAMS FOR EAP STUDENTS IN ISLAMIC HIGHER EDUCATION: PEDAGOGICAL INSIGHTS AND OUTCOMES - Indrawati, Johara; Asmira, Mita (Jurnal Visi Ilmu Pendidikan, 2025)
This research addresses the gap in the literature regarding tailored Extensive Reading Program (ERP) in English for Academic Purposes (EAP) within Islamic higher education. Recognizing the need for context-specific language interventions, the study aimed to investigate the pedagogical insights and outcomes of implementing a Tailored ERP at Universitas Islam Internasional Darullughah Wadda"™wah. The research design involved a survey study with 30 Islamic undergraduate students, employing a close-ended questionnaire divided into three sections to gauge participants' perceptions of the program's structure, relevance of reading materials, and improvements in language and academic skills. Results indicated overwhelmingly positive responses, revealing significant enhancements in reading comprehension, vocabulary acquisition, and critical thinking. The Tailored ERP demonstrated its adaptability in fostering intrinsic motivation, proactive learning, and positive attitudes towards English within an Islamic educational context. The implications of these findings extend to pedagogical practices in EAP, emphasizing the relevance of tailored language programs in diverse cultural and linguistic environments. Limitations include a small sample size and single-institution focus. Future research should explore long-term impacts and transferability to different contexts. This study provides insights for educators seeking effective language interventions in Islamic higher education, highlighting the potential of tailored ERP to cultivate holistic language development and academic engagement.